Metal-loaded HZSM-5 / bentonite composite catalyst as well as preparation method and application thereof

By preparing metal-supported HZSM-5/bentonite composite catalyst, the problems of insufficient selectivity and poor stability of existing catalysts are solved, efficient catalysis of pyrolysis of waste plastics is achieved, and the yield and quality of pyrolytic oil are improved.

CN119565661APending Publication Date: 2025-03-07HONG KONG PRODUCTIVITY COUNCIL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593094.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing catalytic pyrolysis waste plastic catalysts have problems such as insufficient selectivity, poor stability, high requirements for reaction conditions, high costs and poor adaptability to different types of waste plastics.

Method used

The catalyst is prepared by pretreatment, raw material mixing, metal-supported, drying, crushing and screening and calcining using metal-supported HZSM-5/bentonite composite catalyst. This catalyst improves catalytic efficiency and stability by combining transition metals with zeolite and bentonite.

Benefits of technology

The catalyst exhibits high catalytic efficiency at high temperatures for the pyrolytic properties including polypropylene, polystyrene and mixed plastics, and can capture more gasoline and diesel, improving the yield and quality of the pyrolytic oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565661A_ABST
    Figure CN119565661A_ABST
Patent Text Reader

Abstract

The invention relates to a metal-loaded HZSM-5 / bentonite composite catalyst as well as a preparation method and application thereof. The method comprises the following steps: calcining a parent raw material A at 400-600 DEG C for 2-6 hours, and cooling to obtain a parent material A1; mixing the parent material A1 and the parent material B in proportion to obtain a parent material compound A1 / B; immersing the parent raw material compound A1 / B into a metal nitrate solution, stirring and mixing for 2-6 hours at the temperature of 20-70 DEG C, then performing centrifugal separation and cleaning processes, and repeating for 4-6 times to obtain centrifugal solid residues S1; the centrifugal solid residues S1 are dried overnight in a mold, and rod-shaped S1 is obtained; the rod-shaped S1 is crushed in a mortar, and a catalyst precursor material Cat-0 with the particle size of 0.9 mm is screened out; and calcining the catalyst precursor material Cat-0 at 400-600 DEG C for 2-6 hours, and naturally cooling to room temperature to obtain the metal-loaded HZSM-5 / bentonite composite catalyst. The catalyst disclosed by the invention has relatively high catalytic efficiency on pyrolysis performance of polypropylene, polystyrene, mixed plastics and the like, and more gasoline and diesel oil can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a metal-loaded HZSM-5 / bentonite composite catalyst and a preparation method and application thereof. Background Art

[0002] Plastic waste is a pressing global problem. Plastics and microplastics leak into ecosystems and eventually contaminate the food chain. Some studies have shown that microplastics and nanoplastics are present in our drinking water, seafood, and even in the air, potentially posing a serious threat to human and wildlife health. In Hong Kong, China, about 2,100 tons of plastic waste are generated every day, of which less than 15% is recycled (either locally or exported). The rest is discarded in landfills, which are saturated and unsuitable for decomposition or scattered among wildlife.

[0003] In order to prevent environmental pollution and waste of resources, different technical methods such as thermal recovery, biological recovery and chemical recovery have been developed to recycle waste plastics. However, there is still room for improvement and improvement in the existing technology. For example, biological and chemical recovery have the potential to convert waste plastics into monomer materials, but the reaction process is complicated, the yield is low and the cost is high. On the other hand, although thermal treatment technology represented by catalytic pyrolysis technology is currently a large-scale commercial treatment method, in particular, the use of plastic waste pyrolysis to produce fuel oil (PTF) is a technology that has the potential to recycle plastics into useful products on a large scale and reduce the extraction of fossil fuels. This makes PTF a more sustainable solution and a competitive option among green fuels.

[0004] During the pyrolysis process, plastics are treated at high temperatures and in an inert environment to break down the forces between and within molecules. The products of plastic thermal decomposition are char and hydrocarbons of various lengths, such as fuel gas, fuel oil and wax. One of the research directions in this field is how to improve the yield and quality of liquid pyrolysis oil. Al-salem et al. believe that catalytic pyrolysis can optimize the yield and quality of the desired products. The core of this type of technology is the development and utilization of efficient and low-cost catalyst materials. However, the current commercial catalytic pyrolysis of waste plastics catalysts face the following problems: 1. The catalyst has poor selectivity, resulting in unstable product quality, and is easily deactivated at high temperatures, sintering and poisoning. 2. The catalyst usually has high requirements for reaction conditions, which increases the process complexity and energy consumption, and has poor adaptability to different types of waste plastics, making its treatment effect unsatisfactory. 3. The cost of high-performance catalysts is high, the regeneration and recycling process is complicated, and harmful by-products may be generated, affecting the environment. 4. The understanding of the catalytic reaction mechanism is still insufficient, which limits the optimization design of catalysts. Therefore, there is an urgent need to conduct in-depth research and development on catalysts to improve their performance and adaptability and promote the commercial application of catalytic pyrolysis technology of waste plastics. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a metal-loaded HZSM-5 / bentonite composite catalyst and its preparation method and application. The technical problem to be solved is that the existing catalysts for catalytic pyrolysis of waste plastics face multiple problems, including insufficient catalyst selectivity, resulting in unsatisfactory product distribution and stability problems of the catalyst under high temperature and reaction environment, which are prone to deactivation and poisoning. In addition, the existing catalysts have high requirements for reaction conditions, especially temperature, which increases process complexity and energy consumption.

[0006] In order to achieve the above object, the present invention provides a method for preparing a metal-supported HZSM-5 / bentonite composite catalyst, comprising the following steps:

[0007] (1) Pretreatment: calcining the matrix material A at 400-600° C. for 2-6 hours and cooling to obtain the matrix material A1;

[0008] (2) Raw material mixing: the matrix materials A1 and B are mixed according to the proportion to form a matrix raw material composite A1 / B;

[0009] (3) Metal loading: The parent raw material composite A1 / B is immersed in a metal nitrate solution, stirred and mixed at 20-40° C. for 2-6 hours, and then centrifuged and washed 4-6 times to obtain a centrifuged solid residue S1;

[0010] (4) Drying: Dry the solid residue S1 from centrifugation in a mold overnight to obtain a stick-shaped S1;

[0011] (5) Crushing and screening: Crushing the rod-shaped S1 in a mortar, and screening out the catalyst precursor material Cat-0 with a particle size of 0.9 mm;

[0012] (6) Calcination: Calcine the catalyst precursor material Cat-0 at 400-600° C. for 2-6 hours and cool naturally to room temperature to obtain the catalyst Cat-1, i.e., the metal-loaded HZSM-5 / bentonite composite catalyst.

[0013] Preferably, in step (1), the parent materials A and A1 are HZSM-5 and calcined HZSM-5, respectively.

[0014] Preferably, in step (2), B is bentonite, kaolin, montmorillonite, silica gel, bauxite, activated carbon, ceramic material or metal oxide; and the mass mixing ratio of the parent material A1 and B is 30:70-80:20.

[0015] Preferably, in step (3), the metal nitrate is a nitrate of Fe, Ni, Co or Zn; the concentration of the metal nitrate solution is 1.9-2.2 M, and the centrifugal solid residue S1 is a HZSM / bentonite composite material of Fe, Ni, Co or Zn.

[0016] Preferably, in step (4), the mold is a rod-shaped mold, the drying temperature is 70-100° C., and the rod-shaped S1 is a dried HZSM / bentonite composite material of Fe, Ni, Co or Zn.

[0017] Preferably, in step (5), the catalyst precursor material Cat-0 is crushed HZSM / bentonite of Fe, Ni, Co or Zn.

[0018] Preferably, in step (6), the temperature is 400-600° C., the time is 2-6 hours, and the catalyst Cat-1 is a calcined Fe, Ni, Co or Zn-HZSM / bentonite composite catalyst.

[0019] In order to achieve the above object, the present invention also provides a metal-loaded HZSM-5 / bentonite composite catalyst, wherein the metal-loaded HZSM-5 / bentonite composite catalyst is prepared by the above method.

[0020] In order to achieve the above object, the present invention also provides a method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics, comprising the following steps:

[0021] S1 catalytic pyrolysis: The metal-loaded HZSM-5 / bentonite composite catalyst is made into a substrate structure and then catalytically pyrolyzed under nitrogen protection at 400-600°C to obtain a pyrolysis reaction product;

[0022] S2 Product collection: The pyrolysis reaction products are separated to obtain liquid and solid products.

[0023] Preferably, in step S1, the catalytic pyrolysis time is 15-60 minutes.

[0024] Preferably, in step S2, the liquid product is pyrolysis oil, and the solid product is coke.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention forms a catalyst by combining transition metal with zeolite (HZSM type), bentonite, etc. The catalyst has a high catalytic efficiency for the pyrolysis performance of polypropylene (PP), polystyrene (PS), and mixed plastics, etc., and can capture more gasoline and diesel. For pyrolysis oil produced from waste plastics such as polypropylene, in the presence of zeolite, the gasoline series oil in the flask oil increases by 57wt%, while the heavy oil decreases by 42wt%. In addition, the addition of zeolite converts 17wt% of the heavy oil into gasoline distillate oil in the tube oil of the tube furnace. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a schematic structural diagram of a catalytic pyrolysis device according to an embodiment of the present invention;

[0028] Among them, 1-compressed nitrogen tank; 2-nitrogen rotor flowmeter; 3-tubular furnace; 4-quartz boat filled with waste plastics and catalyst; 5-controller; 6-condenser device; 7-cooler water outlet; 8-cooler water inlet; 9-flask. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. The structures, proportions, sizes, etc. shown in the accompanying drawings are only used to match the contents disclosed in the specification so that people familiar with this technology can understand and read them. They are not used to limit the limiting conditions under which the present invention can be implemented, so they have no technical substantive significance. Any structural modification, change in proportional relationship or adjustment of size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention.

[0030] Some embodiments of the present invention provide a method for preparing a metal-supported HZSM-5 / bentonite composite catalyst, comprising the following steps:

[0031] (1) Pretreatment: calcining the parent material A at 400-600°C for 2-6 hours, and obtaining the parent material A1 after cooling; the parent materials A and A1 are HZSM-5 zeolite catalyst and HZSM-5 after calcination, respectively; preferably, the calcination temperature is 450°C, and the calcination time is 4 hours; specifically, the HZSM-5 zeolite catalyst is heated to 400-600°C in a closed furnace at 2-10°C / min and calcined for 2-6 hours, and after the constant temperature calcination is completed and naturally cooled to room temperature, the HZSM-5 is taken out from the muffle furnace;

[0032] (2) Raw material mixing: the parent materials A1 and B are mixed in a mass ratio of 30:70-80:20 to form a parent raw material composite A1 / B; the B may be bentonite, kaolin, montmorillonite, silica gel, bauxite, activated carbon, ceramic material, metal oxide, etc.; preferably, the mixing ratio of the parent materials A1 and B is 70:30;

[0033] (3) Metal loading: A1 / B is immersed in 1.9-2.2M solutions of different metal nitrates, stirred and mixed at 20-40°C for 2-6 hours, and then centrifuged and washed for 4-6 times to obtain a centrifuged solid residue S1; the centrifugal separation speed is 6500-7500 rpm, and the time is 5-10 minutes to optimize solid-liquid separation; the centrifuged solid residue S1 is a Fe(Ni,Co,Zn)-HZSM / bentonite composite material; the stirring process helps to disperse the metal ions on the surface of the catalyst carrier, and at the same time completes the impregnation and aggregation of the metal ions on the carrier.

[0034] Preferably, the metal nitrate is ferric nitrate, the temperature is 30° C., the time is 4 hours, the number of multiple separations is 5 times, and the centrifugal solid residue S1 is a Fe-HZSM / bentonite composite catalyst;

[0035] (4) Drying: Drying S1 in a mold overnight to obtain a rod-shaped (cylindrical) S1; the mold is a conventional rod-shaped mold in the art, the drying temperature is 70-100° C., and the rod-shaped S1 is the dried Fe(Ni,Co,Zn)-HZSM / bentonite composite material;

[0036] Preferably, the rod-shaped S1 is a dried Fe-HZSM / bentonite composite material;

[0037] (5) Crushing and screening: Crushing the rod-shaped S1 in a mortar, and screening out the catalyst precursor material Cat-0 with a particle size of 0.9 mm; the catalyst precursor material Cat-0 is the crushed Fe(Ni,Co,Zn)-HZSM / bentonite;

[0038] Preferably, the catalyst precursor material Cat-0 is a crushed Fe-HZSM / bentonite composite catalyst;

[0039] (6) Calcination: calcine Cat-0 at 400-600°C for 2-6 hours, and naturally cool to room temperature to obtain catalyst Cat-1; the catalyst Cat-1 is a calcined Fe(Ni,Co,Zn)-HZSM / bentonite composite catalyst; preferably, the temperature is 450°C, the time is 4 hours, and the catalyst Cat-1 is a calcined Fe-HZSM / bentonite composite catalyst.

[0040] Some embodiments of the present invention provide a method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics, comprising the following steps:

[0041] S1 catalytic pyrolysis: After the catalyst Cat-1 is prepared into a substrate structure, the mixed waste plastics are catalytically pyrolyzed at 400-600°C under nitrogen protection for 15-60 minutes; preferably, the temperature is 450°C, and the retention temperature of 450°C actually produces the highest flask oil yield (58.5%). The time is 60 minutes, because the yield increases with the reaction time, but after 60 minutes, the reaction yield area is stable and the yield remains above 58%;

[0042] S2 Product Collection: The hydrocarbon vapor after the pyrolysis reaction is condensed into liquid by a condenser device and collected by a round bottom flask. The liquid product is pyrolysis oil.

[0043] Specifically, the method comprises the following steps:

[0044] After the catalyst Cat-1 is prepared into a substrate structure in which the catalyst is dispersed on a piece of quartz wool, it and the waste plastic are respectively loaded into the quartz boat 4;

[0045] The nitrogen in the compressed nitrogen tank 1 is controlled and regulated by the nitrogen rotor flowmeter 2 and is transported to the tubular furnace 3, and serves as a protective gas for the pyrolysis reaction after cleaning the tubular furnace;

[0046] The quartz boat 4 containing waste plastics and catalysts is placed at a suitable position in the tube furnace 3, and the controller 5 controls the temperature rise and heating process of the tube furnace. After all products and catalysts complete the pyrolysis catalytic reaction in the quartz boat 4 containing waste plastics and catalysts, gaseous pyrolysis products are generated;

[0047] The gaseous pyrolysis products generated above are introduced into the condenser device 6. The inlet of the condenser tube of the condenser device 6 is connected to the outlet of the tube furnace 3. The condensation and reflux of the pyrolysis reaction gas products are completed through the water outlet of the cooler water outlet 7 and the water inlet of the cooler water inlet 8. The outlet of the condenser tube is connected to the flask 9 to collect the pyrolysis oil products. Figure 1 shown.

[0048] The present invention is further described below in conjunction with specific embodiments.

[0049] Example 1

[0050] This embodiment provides a method for preparing a metal-supported HZSM-5 / bentonite composite catalyst (wet impregnation method), comprising the following steps:

[0051] 1) Weigh and calcine the HZSM-5 zeolite catalyst in a closed furnace at 5°C / min to 450°C for 4 hours. After the constant temperature calcination is completed and the catalyst is naturally cooled to room temperature, the HZSM-5 is taken out from the muffle furnace.

[0052] 2) The HZSM-5 zeolite catalyst and bentonite are mixed in a mass ratio of 70:30, that is, the two material components in a mixed matrix of 10 g of the HZSM-5 zeolite catalyst and bentonite are in a ratio of 7 g:3 g.

[0053] 3) Dissolve 2.47 g of metal nitrate (Fe(NO3)3·9H2O) in 40 mL of deionized water, and then add the parent material HZSM-5 / bentonite mixture obtained in step 2), followed by magnetic stirring at 30°C for 4 hours and centrifugation at 7000 rpm for 7 minutes, repeated 5 times to remove excess metal nitrate solution.

[0054] 4) The solid mixture (mixed cake) is taken out from the centrifuge tube, and the solid mixture (mixed cake) is dried in a stick-shaped mold overnight to obtain a stick.

[0055] 5) Grind the rod with a mortar and sieve out the catalyst precursor material with a particle size of 0.9 mm; heat the catalyst precursor material to 550°C at 5°C / min in static air and calcine for 4 hours, and cool it naturally to room temperature to obtain the Fe-loaded HZSM-5 / bentonite composite catalyst. Put the Fe-loaded HZSM-5 / bentonite composite catalyst into a dryer and take it out before use to avoid moisture absorption. Collect the Fe-loaded HZSM-5 / bentonite composite catalyst and put it into a small bottle for use when transporting the catalyst, and cover the bottle cap with a film to ensure air tightness.

[0056] Example 2

[0057] The difference between this embodiment and embodiment 1 is that the metal nitrate in step 3) of this embodiment is 3.61 g of Ni(NO3)2·6H2O, and the remaining steps and parameters are the same as those in embodiment 1.

[0058] Example 3

[0059] The difference between this embodiment and embodiment 1 is that the metal nitrate in step 3) of this embodiment is 2.48 g of Co(NO3)2·6H2O, and the remaining steps and parameters are the same as those in embodiment 1.

[0060] Example 4

[0061] The difference between this embodiment and embodiment 1 is that the metal nitrate in step 3) of this embodiment is 2.27 g of Zn(NO3)2·6H2O, and the remaining steps and parameters are the same as those in embodiment 1.

[0062] Application Example 1

[0063] This application example provides a method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics, comprising the following steps:

[0064] Step 1, preparation of substrate:

[0065] 11) Dissolve 1 g of the iron-loaded HZSM-5 / bentonite composite catalyst obtained in Example 1 in 40 ml of deionized water to obtain a catalyst solution; immerse a quartz wool substrate in the obtained catalyst solution, and then slowly lift the quartz wool substrate out of the catalyst solution; the immersion and pulling process needs to ensure that the catalyst is adsorbed on the quartz wool, and rapid pulling will destroy the adsorption, causing the catalyst to desorb and disperse.

[0066] 12) Dry the quartz wool substrate on which the catalyst has been adsorbed in step 11) in air overnight; do not allow the surface of the quartz wool substrate to contact other surfaces to prevent the catalyst from flowing out due to its surface tension rupture; place the dried quartz wool substrate in a drying oven at 70° C. and dry it overnight.

[0067] 13) The quartz wool substrate (containing 1 g of catalyst) dried in step 12) was placed in a muffle furnace and calcined in static air at a temperature of 5° C. / min to 550° C. for 4 hours.

[0068] Step 2: (Catalytic) Pyrolysis of Plastics in a Tube Furnace

[0069] 21) 20 g of a plastic sample (specifically low-density polyethylene) was cut into 1 cm x 1 cm slices.

[0070] 22) Coat the catalyst onto a quartz wool substrate for "substrate" configuration; insert a quartz boat into the quartz tube of a tube furnace, and then put in the quartz wool substrate; put 20 grams of plastic sample into two quartz boats, 10 grams in each quartz boat.

[0071] 23) Place a quartz boat and 1 g of the iron-loaded HZSM-5 / bentonite composite catalyst quartz wool substrate obtained in Example 1 into a quartz tube of a tubular furnace.

[0072] 24) Assemble the tubular pyrolysis furnace device according to the prior art. Perform a bubble test to ensure that the device is leak-free.

[0073] 25) Turn on the cooler and cool the water to 4°C. When the cooler cools the water to 4°C, purge the device with 200 mL / min nitrogen (99.9% purity) flow.

[0074] 26) The plastic sample was pyrolyzed at 450°C for 60 min in a constant 200 mL / min nitrogen flow.

[0075] 27) The pyrolysis vapor product at the outlet of the tube furnace is cooled in a 300 mm condenser with circulating water at 4°C, and the liquid product is condensed and refluxed into a flask; the condensed liquid product is collected from the condenser and the flask and weighed; the residual oil in the tube that is difficult to collect is removed with acetone; the acetone is removed from the sample in a 100°C water bath and the product is obtained, and the obtained product is reweighed to about 11 g.

[0076] The product obtained above was analyzed by GC-FID, and it was found that the yield of pyrolysis oil was 58.5%.

[0077] Application Example 2

[0078] This application example provides a method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics, comprising the following steps:

[0079] Step 1, preparation of substrate:

[0080] 11) Dissolve 1 g of the nickel-loaded HZSM-5 / bentonite composite catalyst obtained in Example 2 in 40 ml of deionized water to obtain a catalyst solution; immerse a quartz wool substrate in the obtained catalyst solution, and then slowly lift the quartz wool substrate out of the catalyst solution; the immersion and pulling process needs to ensure that the catalyst is adsorbed on the quartz wool, and rapid pulling will destroy the adsorption, causing the catalyst to desorb and disperse.

[0081] 12) Dry the quartz wool substrate on which the catalyst has been adsorbed in step 11) in air overnight; do not allow the surface of the quartz wool substrate to contact other surfaces to prevent the catalyst from flowing out due to its surface tension rupture; place the dried quartz wool substrate in a drying oven at 70° C. and dry it overnight.

[0082] 13) The quartz wool substrate (containing 1 g of catalyst) dried in step 12) was placed in a muffle furnace and calcined in static air at a temperature of 5° C. / min to 550° C. for 4 hours.

[0083] Step 2: (Catalytic) Pyrolysis of Plastics in a Tube Furnace

[0084] 21) 20 g of a plastic sample (specifically low-density polyethylene) was cut into 1 cm x 1 cm slices.

[0085] 22) Coat the catalyst onto a quartz wool substrate to prepare a "substrate" configuration; insert a quartz boat into the quartz tube of a tube furnace, and then put in the quartz wool substrate; put 20g of the plastic sample into two quartz boats, 10g in each quartz boat.

[0086] 23) Place a quartz boat and 1 g of the nickel-loaded HZSM-5 / bentonite composite catalyst quartz wool substrate obtained in Example 2 into a quartz tube of a tubular furnace.

[0087] 24) Assemble the tubular pyrolysis furnace device according to the prior art. Perform a bubble test to ensure that the device is leak-free.

[0088] 25) Turn on the cooler and cool the water to 4°C. When the cooler cools the water to 4°C, purge the device with 200 mL / min nitrogen (99.9% purity) flow.

[0089] 26) The plastic sample was pyrolyzed at 450°C for 60 min in a constant 200 mL / min nitrogen flow.

[0090] 27) The pyrolysis vapor product at the outlet of the tube furnace is cooled through a 300 mm condenser tube with 4°C circulating water, and the liquid product is condensed and refluxed into the flask; the condensed liquid product is collected and weighed from the condenser tube and the flask. The residual oil in the tube that is difficult to collect is removed with acetone; the acetone is removed from the sample with a 100°C water bath and the product is obtained, and the obtained product is reweighed to about 11 g.

[0091] The product obtained above was analyzed by GC-FID, and it was found that the pyrolysis oil yield was about 57.5%.

[0092] Application Example 3

[0093] This application example provides a method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics, comprising the following steps:

[0094] Step 1, preparation of substrate:

[0095] 11) Dissolve 1 g of the cobalt-loaded HZSM-5 / bentonite composite catalyst obtained in Example 3 in 40 ml of deionized water to obtain a catalyst solution; immerse a quartz wool substrate in the obtained catalyst solution, and then slowly lift the quartz wool substrate out of the catalyst solution; the immersion and pulling process needs to ensure that the catalyst is adsorbed on the quartz wool, and rapid pulling will destroy the adsorption, causing the catalyst to desorb and disperse.

[0096] 12) Dry the quartz wool substrate on which the catalyst has been adsorbed in step 11) in air overnight; do not allow the surface of the quartz wool substrate to contact other surfaces to prevent the catalyst from flowing out due to its surface tension rupture; place the dried quartz wool substrate in a drying oven at 70° C. and dry it overnight.

[0097] 13) The quartz wool substrate (containing 1 g of catalyst) dried in step 12) was placed in a muffle furnace and calcined in static air at a temperature of 5° C. / min to 550° C. for 4 hours.

[0098] Step 2: (Catalytic) Pyrolysis of Plastics in a Tube Furnace

[0099] 21) Cut 20 g of plastic sample (low-density polyethylene will be torn into strips due to its light weight) into 1 cm x 1 cm slices.

[0100] 22) Coat the catalyst onto a quartz wool substrate for "substrate" configuration; insert a quartz boat into the quartz tube of a tube furnace, and then put in the quartz wool substrate; put 20 grams of plastic sample into two quartz boats, 10 grams in each quartz boat.

[0101] 23) Place the quartz boat and the cobalt-loaded HZSM-5 / bentonite composite catalyst quartz wool substrate obtained in Example 3 into a quartz tube of a tubular furnace.

[0102] 24) Assemble the tubular pyrolysis furnace device according to the prior art. Perform a bubble test to ensure that the device is leak-free.

[0103] 25) Turn on the cooler and cool the water to 4°C. When the cooler cools the water to 4°C, purge the device with 200 mL / min nitrogen (99.9% purity) flow.

[0104] 26) The plastic sample was pyrolyzed at 450°C for 60 min in a constant 200 mL / min nitrogen flow.

[0105] 27) The pyrolysis vapor product at the outlet of the tube furnace is cooled through a 300 mm condenser tube with 4°C circulating water, and the liquid product is condensed and refluxed into the flask; the condensed liquid product is collected and weighed from the condenser tube and the flask. The residual oil in the tube that is difficult to collect is removed with acetone; the acetone is removed from the sample with a 100°C water bath and the product is obtained, and the above-obtained product is reweighed to about 10g.

[0106] The product was analyzed by GC-FID, and the pyrolysis oil yield was about 52.9%.

[0107] Application Example 4

[0108] This application example provides a method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics, comprising the following steps:

[0109] Step 1, preparation of substrate:

[0110] 11) Dissolve 1 g of the zinc-loaded HZSM-5 / bentonite composite catalyst obtained in Example 4 in 40 ml of deionized water to obtain a catalyst solution; immerse a quartz wool substrate in the obtained catalyst solution, and then slowly lift the quartz wool substrate out of the catalyst solution; the immersion and pulling process needs to ensure that the catalyst is adsorbed on the quartz wool, and rapid pulling will destroy the adsorption, causing the catalyst to desorb and disperse.

[0111] 12) Dry the quartz wool substrate on which the catalyst has been adsorbed in step 11) in air overnight; do not allow the surface of the quartz wool substrate to contact other surfaces to prevent the catalyst from flowing out due to its surface tension rupture; place the dried quartz wool substrate in a drying oven at 70° C. and dry it overnight.

[0112] 13) The quartz wool substrate (containing 1 g of catalyst) dried in step 12) was placed in a muffle furnace and calcined in static air at a temperature of 5° C. / min to 550° C. for 4 hours.

[0113] Step 2: (Catalytic) Pyrolysis of Plastics in a Tube Furnace

[0114] 21) 20 g of a plastic sample (specifically low-density polyethylene) was cut into 1 cm x 1 cm slices.

[0115] 22) Coat the catalyst onto a quartz wool substrate for "substrate" configuration; insert a quartz boat into the quartz tube of a tube furnace, and then put in the quartz wool substrate; put 20 grams of plastic sample into two quartz boats, 10 grams in each quartz boat.

[0116] 23) Place a quartz boat and 1 g of the zinc-loaded HZSM-5 / bentonite composite catalyst quartz wool substrate obtained in Example 4 into a quartz tube of a tubular furnace.

[0117] 24) Assemble the tubular pyrolysis furnace device according to the prior art. Perform a bubble test to ensure that the device is leak-free.

[0118] 25) Turn on the cooler and cool the water to 4°C. When the cooler cools the water to 4°C, purge the device with 200 mL / min nitrogen (99.9% purity) flow.

[0119] 26) The plastic sample was pyrolyzed at 450°C for 60 min in a constant 200 mL / min nitrogen flow.

[0120] 27) The pyrolysis vapor product at the outlet of the tube furnace is cooled through a 300 mm condenser tube with 4°C circulating water, and the liquid product is condensed and refluxed into the flask; the condensed liquid product is collected and weighed from the condenser tube and the flask. The residual oil in the tube that is difficult to collect is removed with acetone; the acetone is removed from the sample with a 100°C water bath and the product is obtained, and the obtained product is reweighed to about 10 g.

[0121] The product obtained above was analyzed by GC-FID, and it was found that the pyrolysis oil yield was about 51.5%.

[0122] Application Comparative Example 1

[0123] This comparative example provides a method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics, comprising the following steps:

[0124] Step 1, preparation of substrate:

[0125] 11) Dissolve 1 g of commercial alumina catalyst (Sigma-Aldrich) in 40 ml of deionized water to obtain a catalyst solution; immerse a quartz wool substrate in the obtained catalyst solution, and then slowly lift the quartz wool substrate out of the catalyst solution; the immersion and pulling process needs to ensure that the catalyst is adsorbed on the quartz wool, and rapid pulling will destroy the adsorption, causing the catalyst to desorb and disperse.

[0126] 12) Dry the quartz wool substrate on which the catalyst has been adsorbed in step 11) in air overnight; do not allow the surface of the quartz wool substrate to contact other surfaces to prevent the catalyst from flowing out due to its surface tension rupture; place the dried quartz wool substrate in a drying oven at 70° C. and dry it overnight.

[0127] 13) The quartz wool substrate (containing 1 g of catalyst) dried in step 12) was placed in a muffle furnace and calcined in static air at a temperature of 5° C. / min to 550° C. for 4 hours.

[0128] Step 2: (Catalytic) Pyrolysis of Plastics in a Tube Furnace

[0129] 21) 20 g of a plastic sample (specifically low-density polyethylene) was cut into 1 cm x 1 cm slices.

[0130] 22) Coat the catalyst onto a quartz wool substrate for "substrate" configuration; insert a quartz boat into the quartz tube of a tube furnace, and then put in the quartz wool substrate; put 20 grams of plastic sample into two quartz boats, 10 grams in each quartz boat.

[0131] 23) Place the quartz boat and 1 g of commercial alumina catalyst on a quartz wool substrate into the quartz tube of a tube furnace.

[0132] 24) Assemble the tubular pyrolysis furnace device according to the prior art. Perform a bubble test to ensure that the device is leak-free.

[0133] 25) Turn on the cooler and cool the water to 4°C. When the cooler cools the water to 4°C, purge the device with 200 mL / min nitrogen (99.9% purity) flow.

[0134] 26) The plastic sample was pyrolyzed at 450°C for 60 min in a constant 200 mL / min nitrogen flow.

[0135] 27) The pyrolysis vapor product at the outlet of the tube furnace is cooled through a 300 mm condenser tube with 4°C circulating water, and the liquid product is condensed and refluxed into the flask; the condensed liquid product is collected and weighed from the condenser tube and the flask. The residual oil in the tube that is difficult to collect is removed with acetone; the acetone is removed from the sample with a 100°C water bath and the product is obtained, and the obtained product is reweighed to about 10 g.

[0136] The product obtained above was analyzed by GC-FID, and it was found that the pyrolysis oil yield was about 45%.

[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a metal-supported HZSM-5 / bentonite composite catalyst, characterized in that: The steps include: (1) Pretreatment: calcining the matrix material A at 400-600° C. for 2-6 hours and cooling to obtain the matrix material A1; (2) Raw material mixing: the matrix materials A1 and B are mixed according to the proportion to form a matrix raw material composite A1 / B; (3) Metal loading: The parent raw material composite A1 / B is immersed in a metal nitrate solution, stirred and mixed at 20-70°C for 2-6 hours, and then centrifuged and washed 4-6 times to obtain a centrifuged solid residue S1; (4) Drying: Dry the solid residue S1 from centrifugation in a mold overnight to obtain a stick-shaped S1; (5) Crushing and screening: Crushing the rod-shaped S1 in a mortar, and screening out the catalyst precursor material Cat-0 with a particle size of 0.9 mm; (6) Calcination: Calcine the catalyst precursor material Cat-0 at 400-600° C. for 2-6 hours and cool naturally to room temperature to obtain the catalyst Cat-1, i.e., the metal-loaded HZSM-5 / bentonite composite catalyst.

2. The method for preparing the metal-supported HZSM-5 / bentonite composite catalyst according to claim 1, wherein: In step (1), the matrix material A and the matrix material A1 are HZSM-5 and HZSM-5 after calcination, respectively.

3. The method for preparing the metal-supported HZSM-5 / bentonite composite catalyst according to claim 2, wherein: In step (2), B is bentonite, kaolin, montmorillonite, silica gel, bauxite, activated carbon, ceramic material or metal oxide; the mass mixing ratio of the parent material A1 and B is 30:70-80:

20.

4. The method for preparing the metal-supported HZSM-5 / bentonite composite catalyst according to claim 1, wherein: In step (3), the metal nitrate is a nitrate of Fe, Ni, Co or Zn; the concentration of the metal nitrate solution is 1.9-2.2M, and the centrifugal solid residue S1 is a HZSM / bentonite composite material of Fe, Ni, Co or Zn.

5. The method for preparing the metal-supported HZSM-5 / bentonite composite catalyst according to claim 1, characterized in that: In step (4), the mold is a rod-shaped mold, the drying temperature is 70-100° C., and the rod-shaped S1 is a HZSM / bentonite composite material of Fe, Ni, Co or Zn after drying.

6. The method for preparing the metal-supported HZSM-5 / bentonite composite catalyst according to claim 1, characterized in that: In step (5), the catalyst precursor material Cat-0 is crushed Fe, Ni, Co, or Zn HZSM / bentonite.

7. The method for preparing the metal-supported HZSM-5 / bentonite composite catalyst according to claim 1, characterized in that: In step (6), the temperature is 400-600° C., the time is 2-6 hours, and the catalyst Cat-1 is a calcined Fe, Ni, Co or Zn-HZSM / bentonite composite catalyst.

8. A metal-supported HZSM-5 / bentonite composite catalyst, characterized in that: The metal-supported HZSM-5 / bentonite composite catalyst is prepared by the method according to any one of claims 1 to 7.

9. A method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics, characterized in that: The following steps are involved: S1 catalytic pyrolysis: The metal-loaded HZSM-5 / bentonite composite catalyst is made into a substrate structure and then catalytically pyrolyzed under nitrogen protection at 400-600°C to obtain a pyrolysis reaction product; S2 Product collection: The pyrolysis reaction products are separated to obtain liquid and solid products.

10. The method for preparing fuel oil by catalytic pyrolysis of mixed waste plastics according to claim 9, characterized in that: In step S1, the catalytic pyrolysis time is 15-60 minutes; in step S2, the liquid product is pyrolysis oil, and the solid product is coke.